Five Best Management Practices in High Performing Companies in the Trading Sector of Sri Lanka - Ranasinghe, Sudatta (Journal of Comparative International Management, 1999)
This paper identifies and examines five best management practices of high performing companies in the trading sector. In view of the importance of trade in the gross domestic product of Sri Lanka, an understing of such practices is critical for creating sustained competitive advantage.